2006
DOI: 10.1105/tpc.105.038372
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisPEN3/PDR8, an ATP Binding Cassette Transporter, Contributes to Nonhost Resistance to Inappropriate Pathogens That Enter by Direct Penetration

Abstract: Arabidopsis thaliana is a host to the powdery mildew Erysiphe cichoracearum and nonhost to Blumeria graminis f. sp hordei, the powdery mildew pathogenic on barley (Hordeum vulgare). Screening for Arabidopsis mutants deficient in resistance to barley powdery mildew identified PENETRATION3 (PEN3). pen3 plants permitted both increased invasion into epidermal cells and initiation of hyphae by B. g. hordei, suggesting that PEN3 contributes to defenses at the cell wall and intracellularly. pen3 mutants were compromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
719
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 620 publications
(745 citation statements)
references
References 100 publications
(142 reference statements)
23
719
0
3
Order By: Relevance
“…Although, the abundance of most proteins was not altered by Cd 2+ treatment, peptides 5 corresponding to AtPDR8, an ABC transporter shown to be implicated in pathogen defence [26,27] and heavy metal resistance [28] and the ammonium transporter AtAMT1.1 [29] were present in 3-to 5-fold higher amounts in Cd 2+ treated cell cultures. Despite the fact that the vacuole is the major Cd 2+ store no study has so far investigated whether the abundance of vacuolar membrane proteins changes in response to Cd 2+ stress.…”
Section: Introductionmentioning
confidence: 87%
“…Although, the abundance of most proteins was not altered by Cd 2+ treatment, peptides 5 corresponding to AtPDR8, an ABC transporter shown to be implicated in pathogen defence [26,27] and heavy metal resistance [28] and the ammonium transporter AtAMT1.1 [29] were present in 3-to 5-fold higher amounts in Cd 2+ treated cell cultures. Despite the fact that the vacuole is the major Cd 2+ store no study has so far investigated whether the abundance of vacuolar membrane proteins changes in response to Cd 2+ stress.…”
Section: Introductionmentioning
confidence: 87%
“…One pathway consists of the P450 monooxygenase CYP81F2, the myrosinase PEN2, and the ABC transporter PEN3. CYP81F2 is necessary for the generation of substrates of PEN2, which in turn initiates the metabolism of a group of tryptophan-derived compounds, known as indole glucosinolates, to release potential antimicrobial products by the PEN3 transporter into the extracellular space (Bednarek et al, 2009;Lipka et al, 2005;Stein et al, 2006). The other consists of the PM-anchored syntaxin PEN1, the PM-bound adaptor SNAP33, and the vesicle-associated membrane proteins (VAMPs) 721 and 722 that share 96% identical amino acid sequences (Collins et al, 2003;Kwon et al, 2008c;Pajonk et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that AtPDR8, a member of the pleiotropic drug resistance subfamily of ABC transporters, is involved in both cadmium resistance and pathogen resistance (Kobae et al, 2006;Stein et al, 2006), even though no direct link between pathogen resistance and heavy metals has yet been found (Kim et al, 2007). It has been suggested that AtPDR8 can recognize a very wide range of compounds that may be toxic to the plant cell when accumulated at high concentration, and transport them out of the plasma membrane (Kim et al, 2007).…”
Section: New Phytologistmentioning
confidence: 99%